Rancang Bangun Alat Pencetak Batako Menggunakan Tekanan Kompresor - Yuspian Gunawan; Prinob Aksar (Program Pendidikan Vokasi Teknik Mesin, 2021)
Bricks are bricks made from a mixture of hydraulic adhesives added with fine aggregate and water without any other additives and have a cross-sectional area of ​​the holes of more than 25% of the cross-section of the bricks and the contents of the holes of more than 25% of the contents of the bricks. The purpose of this final project is to design a brick making machine using compressor pressure, design the selection of body materials and frames made of U iron, the main driver is the compressor and the wind work system from the compressor is channeled to the modified car tire pressure tube (tiptop tube) and then assembling the components, namely the frame, car tire pressure tubes (tiptop tubes), brick molds and brick dough container. The final design of the design of the brick making tool uses compressor pressure, namely the brick printing tool is driven by air pressure on the compressor which is connected to a car tire pressure tube (tiptop tube) then will press the mold and produce bricks according to the number of castings.